Impaired renal endothelial nitric oxide synthase and reticulocyte production as modulators of hypertension induced by recombinant human erythropoietin in the rat - Ribeiro, Sandra (2016)
INTRODUCTION AND AIMS: Hypertension is a common side effect of recombinant human erythropoietin (rHuEPO) therapy; however, the exact pathways remain to be elucidated. The discovery of non-hematopoietic actions of rHuEPO increased the number of patients that could putatively benefit from this therapy; however, to achieve those effects higher doses are usually needed, which increase the risk and incidence of adverse events. Our aim was to study the effect of a broad range of rHuEPO doses on hematological and biochemical parameters, blood pressure and renal function and damage in the rat, focusing on endothelial nitric oxide synthase (eNOS) and hypoxia-inducible factors (HIFs). METHODS: Male Wistar rats were divided in 5 groups receiving different doses of rHuEPO (100, 200, 400 and 600 IU/kg body weight (BW)/week) and saline solution (control), during 3 weeks. Blood and 24h urine were collected to perform hematological and biochemical analysis. Blood pressure (BP) was measured by the tail-cuff method. The kidney tissue was collected to mRNA and protein expression assays and to characterize renal lesions. RESULTS: A dose-dependent increase in red blood cells count, hematocrit and hemoglobin levels was found with rHuEPO therapy, in rHuEPO200, rHuEPO400 and rHuEPO600 groups. Increased reticulocyte count was found in the rHuEPO400 and rHuEPO600 groups. BP raised in all groups receiving rHuEPO. The rHuEPO200 and rHuEPO600 groups presented increased kidney protein levels of HIF2α and a reduction in kidney protein levels of eNOS, along with the highest grade of vascular and tubular renal lesions. CONCLUSIONS: Our study showed that rHuEPO-induced hypertension might involve indirect (hematological) and direct (renal) effects which varies according to the dose used. Thus, rHuEPO therapy should be performed rationally and under adequate surveillance, as hypertension develops even with lower doses. Especial caution with higher doses should be taken, as rHuEPO-induced hypertension leads to early renal damage without alterations in traditional markers of renal function, thus masking the serious adverse effects and risks.